Low dose ketamine reduces pain perception and blood pressure, but not muscle sympathetic nerve activity, responses during a cold pressor test. (20th October 2020) - Watso, Joseph C.; Huang, Mu; Moralez, Gilbert; Cramer, Matthew N.; Hendrix, Joseph M.; Cimino, Frank A.; Belval, Luke N.; Hinojosa‐Laborde, Carmen; Crandall, Craig G.
Abstract : Key points: Low dose ketamine is a leading medication used to provide analgesia in pre‐hospital and hospital settings. Low dose ketamine is increasingly used off‐label to treat conditions such as depression. In animals, ketamine stimulates the sympathetic nervous system and increases blood pressure, but these physiological consequences have not been studied in conscious humans. Our data suggest that low dose ketamine administration blunts pain perception and reduces blood pressure, but not muscle sympathetic nerve activity burst frequency, responses during a cold pressor test in healthy humans. These mechanistic, physiological results inform risk‐benefit analysis for clinicians administering low dose ketamine in humans. Abstract: Low dose ketamine is an effective analgesic medication. However, our knowledge of the effects of ketamine on autonomic cardiovascular regulation is primarily limited to animal experiments. Notably, it is unknown if low dose ketamine influences autonomic cardiovascular responses during painful stimuli in humans. We tested the hypothesis that low dose ketamine blunts perceived pain, and blunts subsequent sympathetic and cardiovascular responses during an experimental noxious stimulus. Twenty‐two adults (10F/12M; 27 ± 6 years; 26 ± 3 kg m −2, mean ± SD) completed this randomized, crossover, placebo‐controlled trial during two laboratory visits. During each visit, participants completed cold pressor tests (CPT; hand in ∼0.4°C ice bath for 2 min) pre‐ and 5 min post‐drug administration (20 mg ketamine or saline). We compared pain perception (100 mm visual analogue scale), muscle sympathetic nerve activity (MSNA; microneurography, 12 paired recordings), and beat‐to‐beat blood pressure (BP; photoplethysmography) during the pre‐ and post‐drug CPTs separately using paired, two‐tailed t tests. For the pre‐drug CPT, perceived pain ( P = 0.4378), MSNA burst frequency responses ( P = 0.7375), and mean BP responses ( P = 0.6457) were not different between trials. For the post‐drug CPT, ketamine compared to placebo administration attenuated perceived pain ( P < 0.0001) and mean BP responses ( P = 0.0047), but did not attenuate MSNA burst frequency responses ( P = 0.3662). Finally, during the post‐drug CPT, there was a moderate relation between cardiac output and BP responses after placebo administration ( r = 0.53, P = 0.0121), but this relation was effectively absent after ketamine administration ( r = −0.12, P = 0.5885). These data suggest that low dose ketamine administration attenuates perceived pain and pressor, but not MSNA burst frequency, responses during a CPT. Key points: Low dose ketamine is a leading medication used to provide analgesia in pre‐hospital and hospital settings. Low dose ketamine is increasingly used off‐label to treat conditions such as depression. In animals, ketamine stimulates the sympathetic nervous system and increases blood pressure, but these physiological consequences have not been studied in conscious humans. Our data suggest that low dose ketamine administration blunts pain perception and reduces blood pressure, but not muscle sympathetic nerve activity burst frequency, responses during a cold pressor test in healthy humans. These mechanistic, physiological results inform risk‐benefit analysis for clinicians administering low dose ketamine in humans.